Workshop DUXAIT: Conducting Efficient Heuristic Evaluations with the Duxait-Ng Tool. A Case Study - (:unkn) unknown (Springer Nature Switzerland, 2024)
In the context of Covid-19 pandemic, conducting a user experience evaluation has become more. For example, Heuristic Evaluation, is manual task-dependent, does not have a standardized way, and data processing costs valuable time. This context made heuris...
Keywords: Evaluación heurística; DUXAIT